Global Protein Expression Analysis of Molecular Markers of DS-1-47,a Component of Implantation-promoting Traditional Chinese Medicine - 李彦玲 章晓燕 冷宇 吴艳丽 李靖 吴云霞 (华中科技大学学报：医学英德文版, 2016)
This study investigated the molecular markers of DS-1-47,a component of an implantation-promoting traditional Chinese medicine consisting of Astragalus mongholicus,Atractylodes macrocephala,Scutellaria baicalensis and Dipsacales,in an attempt to clarify the molecular mechanism and action targets of DS-1-47.Controlled ovarian stimulation(COS) method was used to establish the implantation dysfunction models of mice.Animals were divided into normal pregnant group,COS model group and DS-1-47 group.Laser capture microdissection-double dimensional electrophoresis-mass spectrum(LCM-DE-MS) was used to analyze the uterine protein molecules that were possibly involved in the promotion of implantation.Twenty-three proteins in DS-1-47 group were significantly changed as compared to those in COS model group,with 7 proteins down-regulated and 16 proteins up-regulated.Except for some constituent proteins,the down-regulated proteins included collagen α-1(Ⅵ) chain,keratin 7,keratin 14,myosin regulatory light chain 12 B,myosin light polypeptide 9,heat shock protein β-7,and C-U-editing enzyme APOBEC-2;the up-regulated proteins included apolipoprotein A-I,calcium regulated protein-3,proliferating cell nuclear antigen,L-xylulose reductase,and calcium binding protein.These 23 proteins that were regulated by DS-1-47 represented a broad diversity of molecule functions.The down-regulated proteins were associated with stress and immune response,and those up-regulated proteins were related to proliferation.It was suggested that these proteins were important in regulating the uterine environment for the blastocyst implantation.By identification of DS-1-47 markers,proteomic analysis coupled with functional assays is demonstrated to be a promising approach to better understand the molecular mechanism of traditional Chinese medicine.